Analysing Arbitration Laws across Legal Systems - Bhatia, Vijay K.; Candlin, Christopher N. (HERMES - Journal of Language and Communication in Business, 2004)
In this paper, the national Indian and Chinese statutes on arbitration are compared with the UNCITRAL Model Law. After a presentation of the GILD-MMC project, focus is especially on textual aspects indicating attitudes towards the relation between the administrative powers and the parties in commercial arbitration. Thus, looking at the features all-inclusiveness, information load, information spread, legislative style and transparency signiﬁ cant differences are found and related to the different com municative purposes (overall model vs. speciﬁ c national rules), the different legal traditions (common law vs. civil law) and the different political systems (westernised market economy vs. socialist market economy).